Multi-Market Antitrust Economics - Gilbert, Scott (Quantitative Perspectives on Behavioral Economics and Finance,, 2018)
Antitrust economics is a field that draws extensively on the economic theory of industrial organization, and the field's frontier is at the cutting edge of economic research. This book bridges the gap between introductory texts and advanced research volumes by presenting select themes in antitrust economics and modeling. All from a neoclassical perspective, the author begins by discussing classic monopoly, continues to add more markets to the mix-via spillover effects and horizontal/vertical mergers-and then explores logical ties to international trade and regulated industries. While brief and selective, the method provides a basic analytical reference point for approaching special antitrust topics not covered here, such as tying, bundling, and exclusive dealing. Such analytics are sometimes likened to a rational defense of monopoly and related anti-competitive behavior, but are essential to explicating antitrust economics from a mainstream Western economic vantage.